Platelet interaction and performance of antibacterial bioinspired nanostructures passivated with human plasma - Anouck L.S. Burzava; Agnieszka Zuber; Andrew Hayles; James Morel; Richard Bright; Jonathan Wood; Dennis Palms; Dan Barker; Toby Brown; Krasimir Vasilev (Materials Today Bio)
The ever-increasing ageing of the world population is demanding superior orthopedic devices. Issues such as implant infection, poor osseointegration, or chronic inflammation remain problematic to the lifespan and long-term efficacy of implants. Fabrication of materials with bioinspired nanostructures is one emerging antibacterial strategy to prevent implant infection, however their interactions with blood components, and whether they retain their bactericidal properties in an environment displaying a complex protein corona, remains largely unexplored. In the present study, titanium alloy, commercially pure and plasma-sprayed titania were hydrothermally etched, passivated with human native plasma to develop a protein corona, and then incubated with either Staphylococcus aureus, Pseudomonas aeruginosa or human platelets. Surface analysis was first used to characterize the topography, chemical composition or crystallinity of each material. Fluorescence staining and SEM were performed to evaluate the nanostructure bactericidal properties, as well as to study platelet attachment and morphology. Composition of platelet supernatant was studied using ELISA and flow cytometry. Overall, our study showed that the bioinspired nanostructured surfaces displayed both impressive antibacterial properties in a complex environment, and a superior blood biocompatibility profile in terms of platelet activation (particularly for titanium alloy). Additionally, the amount of pro-inflammatory cytokines released by platelets was found to be no different to that found in native plasma (background levels) and, in some cases, presented a more pro-healing profile with an increased secretion of factors such as TGF-β, PDGF-BB or BMP-2. The nanostructured surfaces performed equally, or better, than hydroxyapatite-coated titanium which is one of the current gold standards in orthopedics. Although further in vivo studies are required to validate these results, such bioinspired nanostructured surfaces certainly show promise to be safely applied to medical device surfaces used in orthopedics and other areas.